Heart Enhancers: Development and Disease Control at a Distance - Yuan, Xuefei; Scott, Ian C.; Wilson, Michael D. (Frontiers in Genetics, 2021)
Bound by lineage-determining transcription factors and signaling effectors, enhancers play essential roles in precisely controlling spatiotemporal gene expression profiles during development, homeostasis and disease. Recent synergistic advances in functional genomic technologies, combined with the developmental biology toolbox, have resulted in unprecedented genome-wide annotation of heart enhancers and their target genes. Starting with early studies of vertebrate heart enhancers and ending with state-of-the-art genome-wide enhancer discovery and testing, we will review how studying heart enhancers in metazoan species has helped inform our understanding of cardiac development and disease.